Media accessibility training - Mazur, Iwona; Vercauteren, Gert (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
With the emergence of media accessibility services such as audio description and (live) subtitles for the deaf and the hard of hearing the need has arisen to train prospective professionals in those areas. In this article, which opens the volume devoted to media accessibility training, we first define the field of study and then review some European projects that deal with the topic. Next, we discuss the current landscape of media accessibility training, including the required skills and competences, curriculum design, methodological approaches, training materials and assessment. An overview of the 12 contributions that have been included in the volume follows, together with an exploration of how they advance the state of the art. Finally, we end with a note on what still remains to be done in the realm of media accessibility training.